Herramientas digitales en el ejercicio periodístico. Caso El Vocero. Babahoyo 2020 - López Zamora, Karla Dayanna (2020)
In carrying out this case study, the objective of this case study is to analyze the digital tools used in journalism by the communicators of the digital newspaper "El Vocero" from Babahoyo during the social distancing of the year 2020, which makes use of these digital tools at the moment to record a journalist note, create images, videos, texts, for the organization and coordination of the medium, in addition to keeping its readers informed through social networks such as: Facebook, Instagram and Twitter. The technique that was applied is the interview, a questionnaire of 10 questions was raised based on the study phenomenon, taking into account that the Online communication medium "El Vocero" work four journalists, it was determined that the information for the research study It would be facilitated by the Degree in Communication María Teresa Flores Montoya, director of the digital medium, the interview was carried out through the Google meet platform to protect the respondent due to the problem of social distancing, Covid-19. Digital tools facilitate the journalist's work, helping to improve the quality of their content to post on social media, obtain direct information from the community, organization and writing of the medium, in addition to using this tool in the coverage of a news item through a camera, audio recorder, tripod and smartphone.